Perjuangan perundangan pengguna - Mohd. Hamdan Haji Adnan, Dato'; Malaysia (Petaling Jaya : IBS Buku, 2005)
Consumer rights in Malaysia
Includes bibliographical references (p. 163-164)
In Malay
Keywords: Consumer protection -- Law and legislation -- Malaysia